Effect of Arbuscular Mycorrhizal Fungi Based Biofertilizer on Coconut Seedlings Growth in Nursery - Senarathne , S. H. S.; Ilangamudali, I. M. P. S. (International Coconut Community, 2018)
The success of a coconut plantation, in terms of its field establishment as well as its future performance, is heavily dependent on the quality of the seedlings used. Coconut nurseries adopt different agronomic practices to produce good quality seedlings. Applying mycorrhizal inoculants is becoming an increasingly common practice in plant nurseries as it facilitates healthy seedling growth resulting in healthy and vigorous seedlings in the nursery, helps to reduce mortality rates of seedlings in the field and reduce water and fertilizer consumption. In this study effects of mycorrhizae based biofertilizer were evaluated for the growth of coconut seedlings in the nursery and field. The experiment was conducted at the Makadura Research Center in Sri Lanka. The nursery experiment treatments were, the presence of AMF based biofertilizer (50g per seedling or per bag) and absence of mycorrhizae based biofertilizer. In the field experiment, five treatments with 500g of AMF biofertilizerwith 25% recommended inorganic fertilizer mixture for young coconut palms (YPM) per seedling, 500g of AMF biofertilizer with 50% YPM per seedling, 500g of AMF biofertilizer with 75% YPM per seedling, 500g of AMF biofertilizer with 100% YPM per seedling and with only YPM per seedling. Root and shoot growth of seedlings were measured at monthly intervals in the nursery experiment. Leaf production rate and stem girth of the seedling were measured at six months interval in the field experiment. The application of bio fertilizer increased the volume and dry weight of primary, secondary, tertiary and quaternary roots in seedlings in the nursery significantly. A significantly higher leaf production rate and stem girth was observed in the field seedlings treatment with 500g of AMF biofertilizer with 75% YPM. The experiment concluded that application of bio fertilizer is beneficial for coconut seedlings in the nursery for the production good quality seedlings with well-developed roots resulting in better field establishment and in the field for fast and vigorous growth.